Plant RNA Interactome Capture: Revealing the Plant RBPome. (June 2017) - Bach-Pages, Marcel; Castello, Alfredo; Preston, Gail M.
Abstract : The application of RNA interactome capture to plants has enabled comprehensive determination of the plant RNA-binding proteome and the identification of novel families of RNA-binding proteins (RBPs). The technique is providing insight into the evolution of the eukaryotic repertoire of RBPs and will enhance prospects for engineering RBPs to improve crop traits.